Intrinsically Low Thermal Conductivity in the Most Lithium-Rich Binary Stannide Crystalline Li5Sn - Tong, Zhen; Dumitrică, Traian; Frauenheim, Thomas (The journal of physical chemistry letters, 2023)
Using ab initio lattice dynamics and a unified heat transport theory, we compute the lattice thermal conductivity (κ L ) of Li5Sn, a newly synthesized crystalline material for Li-ion batteries. The weak bonding in the Li-rich environment leads to significant softening of the optical phonon modes, temperature-induced hardening, and strong anharmonicity. This complexity is captured in the particle-like and glass-like components of κ L by accounting for the temperature-dependent interatomic force constants acting on the renormalized phonon frequencies and three- and four-phonon scatterings contributing to the phonon lifetime. We predict very low room-temperature κ L values of 0.857, 0.599, and 0.961 W/mK for the experimental Cmcm phase and 0.996, 0.908, and 1.385 W/mK for the theoretically predicted Immm phase along the main crystallographic directions. Both phases display complex crystal behavior with glass-like transport exceeding 20% above room-temperature and an unusual κ L temperature dependence. Our results can be used to inform system-level thermal models of Li-ion batteries.